Trifluoperazine, a Well-Known Antipsychotic, Inhibits Glioblastoma Invasion by Binding to Calmodulin and Disinhibiting Calcium Release Channel IP3R - Kang, Seokmin; Hong, Jinpyo; Lee, Jung Moo; Moon, Hyo Eun; Jeon, Borami; Choi, Jungil; Yoon, Nal Ae; Paek, Sun Ha; Roh, Eun Joo; Lee, C. Justin; Kang, Sang Soo (AMER ASSOC CANCER RESEARCH, 2017)
Calcium (Ca2+) signaling is an important signaling process, implicated in cancer cell proliferation and motility of the deadly glioblastomas that aggressively invade neighboring brain tissue. We have previously demonstrated that caffeine blocks glioblastoma invasion and extends survival by inhibiting Ca2+ release channel inositol 1,4,5-trisphosphate receptor (IP3R) subtype 3. Trifluoperazine (TFP) is an FDA-approved antipsychotic drug for schizophrenia. Interestingly, TFP has been recently reported to show a strong anticancer effect on lung cancer, hepatocellular carcinoma, and T-cell lymphoma. However, the possible anticancer effect of TFP on glioblastoma has not been tested. Here, we report that TFP potently suppresses proliferation, motility, and invasion of glioblas-toma cells in vitro, and tumor growth in in vivo xenograft mouse model. Unlike caffeine, TFP triggers massive and irreversible release of Ca2+ from intracellular stores by IP3R subtype 1 and 2 by directly interacting at the TFP-binding site of a Ca2+-binding protein, calmodulin subtype 2 (CaM2). TFP binding to CaM2 causes a dissociation of CaM2 from IP3R and subsequent opening of IP3R. Compared with the control neural stem cells, various glioblastoma cell lines showed enhanced expression of CaM2 and thus enhanced sensitivity to TFP. On the basis of these findings, we propose TFP as a potential therapeutic drug for glioblastoma by aberrantly and irreversibly increasing Ca2+ in glioblastoma cells. (C) 2016 AACR.
Keywords: ADJUVANT TEMOZOLOMIDE; GROWTH-INHIBITION; CELL-CYCLE; CANCER; SURVIVAL; DRUGS; RADIOTHERAPY; CONCOMITANT; RESISTANCE; INDUCTION